Sharia Bank Information Systems in the Context of Value Chain Financing - Suriani, Seri -; Baharuddin, Sitti Mujahida Baharuddin Mujahida; Nur, Indrayani; Abubakar, Herminawaty; Sukmawati, Sukmawati (Universitas Dharma Wacana, 2023)
This research aims to test and analyze the financing value chain at Bank Syariah Indonesia. The population is sharia banking in Indonesia. The results of the research state that based on the existing research problem formulation and data analysis that has been carried out regarding Value Chain Analysis based on sharia principles, several things can be concluded, namely: the application of the Value Chain Analysis concept with a sharia principle approach to activities. Good Corporate Governance has 5 principles that are used to realize good corporate governance.